Parents’ Role in Children's Learning During and After the Covid-19 Pandemic - Budi Rahardjo; Fachrul Rozie; Jessika Maulina (Jurnal Pendidikan Usia Dini, 2022)
When children only see their friends in little squares via Google Meet or Zoom, can teachers really address concepts like the importance of teamwork or how to manage conflict?  This is a learning phenomenon during the COVID-19 pandemic and the era after it. This study aims to see the role of parents as children's learning companions in terms of mentors and motivators when online education takes place. This research using photovoice within phenomenological methodology and have been doing with thematic analysis and collecting data through interviews and observations. The participants were eight parents and one female teacher as a homeroom teacher. The research findings show that although there are many obstacles in online learning for children, learning during the COVID-19 pandemic can still run by involving the role of parents and teachers as pillars of education for preschool-age children. For further research, it is hoped that the findings will be a way in solving learning problems for children.Keywords: early childhood education, parents’ role, online learningReferences:Adedoyin, O. B., & Soykan, E. (2020). Covid-19 pandemic and online learning: The challenges and opportunities. In Interactive Learning Environments. https://doi.org/10.1080/10494820.2020.1813180Aras, S. (2016). Free play in early childhood education: A phenomenological study. Early Child Development and Care, 186(7). https://doi.org/10.1080/03004430.2015.1083558Arkorful, V. (2021). The role of e-learning, advantages and disadvantages of its adoption in higher The role of e-learning, the advantages and disadvantages of its adoption in Higher Education . International Journal of Education and Research, 2(December 2014).Atiles, J. T., Almodóvar, M., Chavarría Vargas, A., Dias, M. J. A., & Zúñiga León, I. M. (2021). International responses to COVID-19: Challenges faced by early childhood professionals. European Early Childhood Education Research Journal, 29(1). https://doi.org/10.1080/1350293X.2021.1872674Barnett, W. S., Grafwallner, R., & Weisenfeld, G. G. (2021). Corona pandemic in the United States shapes new normal for young children and their families. In European Early Childhood Education Research Journal (Vol. 29, Issue 1). https://doi.org/10.1080/1350293X.2021.1872670Basham, J. D., Blackorby, J., & Marino, M. T. (2020). Opportunity in Crisis: The Role of Universal Design for Learning in Educational Redesign. In Learning Disabilities: A Contemporary Journal (Vol. 18, Issue 1).Beatriks Novianti Bunga, R. Pasifikus Christa Wijaya & Indra Yohanes Kiling (2021) Studying at Home: Experience of Parents and Their Young Children in an Underdeveloped Area of Indonesia, Journal of Research in Childhood Education, DOI: 10.1080/02568543.2021.1977436Buheji, M., Hassani, A., Ebrahim, A., da Costa Cunha, K., Jahrami, H., Baloshi, M., & Hubail, S. (2020). Children and Coping During COVID-19: A Scoping Review of Bio-Psycho-Social Factors. International Journal of Applied Psychology, 10(1). https://doi.org/10.5923/j.ijap.20201001.02Celik, M. Y. (2021). The dual role of nurses as mothers during the pandemic period: Qualitative study. Early Child Development and Care. https://doi.org/10.1080/03004430.2021.1917561Coulter, M., Britton, Ú., MacNamara, Á., Manninen, M., McGrane, B., & Belton, S. (2021). PE at Home: Keeping the ‘E’ in PE while home-schooling during a pandemic. Physical Education and Sport Pedagogy. https://doi.org/10.1080/17408989.2021.1963425Creswell, J. W. (2015). Educational research: Planning, conducting, and evaluating quantitative and qualitative research (Fifth edition). Pearson.Dodd, H. F., Fitzgibbon, L., Watson, B. E., & Nesbit, R. J. (2021). Children’s play and independent mobility in 2020: Results from the british children’s play survey. International Journal of Environmental Research and Public Health, 18(8). https://doi.org/10.3390/ijerph18084334Duran, A. (2019). A Photovoice Phenomenological Study Exploring Campus Belonging for Queer Students of Color. Journal of Student Affairs Research and Practice, 56(2). https://doi.org/10.1080/19496591.2018.1490308Ebbeck, M., Yim, H. Y. B., Chan, Y., & Goh, M. (2016). Singaporean Parents’ Views of Their Young Children’s Access and Use of Technological Devices. Early Childhood Education Journal. https://doi.org/10.1007/s10643-015-0695-4Ekyana, Luluk, Fauziddin Muhammad & Arifiyanti Nurul. (2021). Parents’ Perception: Early Childhood Social Behaviour During Physical Distancing in the Covid-19 Pandemic. JPUD: Jurnal Pendidikan Usia Dini, Volume 15 (2),DOI: https://doi.org/10.21009/JPUD.152.04Eslava, M., Deaño, M., Alfonso, S., Conde, Á., & García-Señorán, M. (2016). Family context and preschool learning. Journal of Family Studies, 22(2). https://doi.org/10.1080/13229400.2015.1063445Finn, L., & Vandermaas-Peeler, M. (2013). Young children’s engagement and learning opportunities in a cooking activity with parents and older siblings. Early Childhood Research and Practice, 15(1).Gee, E., Siyahhan, S., & Cirell, A. M. (2017). Video gaming as digital media, play, and family routine: Implications for understanding video gaming and learning in family contexts. Learning, Media, and Technology, 42(4). https://doi.org/10.1080/17439884.2016.1205600Gelir, I., & Duzen, N. (2021). Children’s changing behaviours and routines, challenges and opportunities for parents during the COVID-19 pandemic. Education 3-13. https://doi.org/10.1080/03004279.2021.1921822Giannini, S., Jenkins, R., & Saavedra, J. (2021). Mission: Recovering Education 2021. In UNICEF, UNESCO, and World Bank.Goodhart, F. W., Hsu, J., Baek, J. H., Coleman, A. L., Maresca, F. M., & Miller, M. B. (2006). A view through a different lens: Photovoice as a tool for student advocacy. Journal of American College Health, 55(1). https://doi.org/10.3200/JACH.55.1.53-56Gong, S., Wang, X., Wang, Y., Qu, Y., Tang, C., Yu, Q., & Jiang, L. (2019). A descriptive qualitative study of home care experiences in parents of children with tracheostomies. Journal of Pediatric Nursing, 45. https://doi.org/10.1016/j.pedn.2018.12.005Hamaidi, D. A., Arouri, Y. M., Noufa, R. K., & Aldrou, I. T. (2021). Parents’ Perceptions of Their Children’s Experiences with Distance Learning During the COVID-19 Pandemic. International Review of Research in Open and Distance Learning, 22(2). https://doi.org/10.19173/irrodl.v22i2.5154Hammersley, M., & Traianou, A. (2015). Ethics in Qualitative Research: Controversies and Contexts. In Ethics in Qualitative Research: Controversies and Contexts. https://doi.org/10.4135/9781473957619Harris, K. I. (2021). Parent Cooperative Early Childhood Settings: Empowering Family Strengths and Family Engagement for All Young Children. International Journal of Contemporary Education, 4(1). https://doi.org/10.11114/ijce.v4i1.5143Hassinger-Das, B., Zosh, J. M., Hansen, N., Talarowski, M., Zmich, K., Golinkoff, R. M., & Hirsh-Pasek, K. (2020). Play-and-learn spaces: Leveraging library spaces to promote caregiver and child interaction. Library and Information Science Research, 42(1). https://doi.org/10.1016/j.lisr.2020.101002Henter, R., & Nastasa, L. E. (2021). Parents’ Emotion Management for Personal Well-Being When Challenged by Their Online Work and Their Children’s Online School. Frontiers in Psychology, 12. https://doi.org/10.3389/fpsyg.2021.751153Houston, S. (2017). Towards a critical ecology of child development in social work: Aligning the theories of Bronfenbrenner and Bourdieu. Families, Relationships and Societies, 6(1). https://doi.org/10.1332/204674315X14281321359847Ihmeideh, F., AlFlasi, M., Al-Maadadi, F., Coughlin, C., & Al-Thani, T. (2020). Perspectives of family–school relationships in Qatar based on Epstein’s model of six types of parent involvement. Early Years, 40(2). https://doi.org/10.1080/09575146.2018.1438374Iruka, I. U., DeKraai, M., Walther, J., Sheridan, S. M., & Abdel-Monem, T. (2020). Examining how rural ecological contexts influence children’s early learning opportunities. Early Childhood Research Quarterly, 52. https://doi.org/10.1016/j.ecresq.2019.09.005Jiles, T. (2015). Knock, knock, may I come in? An integrative perspective on professional development concerns for home visits conducted by teachers. Contemporary Issues in Early Childhood, 16(1). https://doi.org/10.1177/1463949114567274Kartini, K. (2021). Analisis Pembelajaran Online Anak Usia Dini Masa Pandemi COVID -19 Kota dan Perdalaman. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 6(2). https://doi.org/10.31004/obsesi.v6i2.880Kurniati, E., Nur Alfaeni, D. K., & Andriani, F. (2020). Analisis Peran Orang Tua dalam Mendampingi Anak di Masa Pandemi Covid-19. Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 5(1). https://doi.org/10.31004/obsesi.v5i1.541La Paro, K. M., & Gloeckler, L. (2016). The Context of Child Care for Toddlers: The “Experience Expectable Environment”. Early Childhood Education Journal, 44(2). https://doi.org/10.1007/s10643-015-0699-0Lau, E. Y. H., & Lee, K. (2021). Parents’ Views on Young Children’s Distance Learning and Screen Time During COVID-19 Class Suspension in Hong Kong. Early Education and Development, 32(6). https://doi.org/10.1080/10409289.2020.1843925Lau, E. Y. H., Li, J. Bin, & Lee, K. (2021). Online Learning and Parent Satisfaction during COVID-19: Child Competence in Independent Learning as a Moderator. Early Education and Development, 32(6). https://doi.org/10.1080/10409289.2021.1950451Lilawati, A. (2020). Peran Orang Tua dalam Mendukung Kegiatan Pembelajaran di Rumah pada Masa Pandemi. Jurnal Obsesi: Jurnal Pendidikan Anak Usia Dini. https://doi.org/10.31004/obsesi.v5i1.630Lim, K. F. (2020). Emergency remote teaching and learning in the time of COVID-19. Chemistry in Australia, August.Lin, X., & Li, H. (2018). Parents’ play beliefs and engagement in young children’s play at home. European Early Childhood Education Research Journal, 26(2). https://doi.org/10.1080/1350293X.2018.1441979Michele L. Stites, Susan Sonneschein & Samantha H. Galczyk (2021) Preschool Parents’ Views of Distance Learning during COVID-19, Early Education and Development, 32:7, 923-939, DOI: 10.1080/10409289.2021.1930936Muhdi, Nurkolis, & Yuliejantiningsih, Y. (2020). The Implementation of Online Learning in Early Childhood Education During the Covid-19 Pandemic. JPUD - Jurnal Pendidikan Usia Dini, 14(2). https://doi.org/10.21009/jpud.142.04Ortlipp, M. (2015). Keeping and Using Reflective Journals in the Qualitative Research Process. The Qualitative Report. https://doi.org/10.46743/2160-3715/2008.1579Paat, Y. F. (2013). Working with Immigrant Children and Their Families: An Application of Bronfenbrenner’s Ecological Systems Theory. Journal of Human Behavior in the Social Environment, 23(8). https://doi.org/10.1080/10911359.2013.800007Plowman, L., Stephen, C., & McPake, J. (2010). Supporting young children’s learning with technology at home and in preschool. Research Papers in Education, 25(1). https://doi.org/10.1080/02671520802584061Rona Novick, Suzanne Brooks & Jenny Isaacs (2021) Parental Report of Preschoolers’ Jewish Day School Engagement and Adjustment During the Covid-19 Shutdown, Journal of Jewish Education, 87:4, 301-315, DOI: 10.1080/15244113.2021.1977098Sandi Ferdiansyah, S. S., & Angin, R. (2020). Pengalaman Mahasiswa Thailand dalam Pembelajaran Daring di Universitas di Indonesia pada Masa Pandemi COVID-19. Journal of International Students, 10(S3).Sonnenschein, S., Stites, M., & Dowling, R. (2021). Learning at home: What preschool children’s parents do and what they want to learn from their children’s teachers. Journal of Early Childhood Research, 19(3). https://doi.org/10.1177/1476718X20971321Sri Indah Pujiastuti, Sofia Hartati & Jun Wang (2022) Socioemotional Competencies of Indonesian Preschoolers: Comparisons between the Pre-Pandemic and Pandemic Periods and among DKI Jakarta, DI Yogyakarta and West Java Provinces, Early Education and Development, DOI: 10.1080/10409289.2021.2024061Stone, K., Burgess, C., Daniel, B., Smith, J., & Stephen, C. (2017). Nurture corners in preschool settings: Involving and nurturing children and parents. Emotional and Behavioural Difficulties, 22(4). https://doi.org/10.1080/13632752.2017.1309791Suzanne M. Egan & Chloé Beatty (2021) To school through the screens: the use of screen devices to support young children's education and learning during the COVID-19 pandemic, Irish Educational Studies, 40:2, 275-283, DOI: 10.1080/03323315.2021.1932551Thomson, S. (2007). Do’s and don’ts: Children’s experiences of the primary school playground. Environmental Education Research, 13(4). https://doi.org/10.1080/13504620701581588Vallejo-Ruiz, M., & Torres-Soto, A. (2020). Teachers’ conceptions on the quality of the teaching and learning process in early childhood education. Revista Electronica Educare, 24(3). https://doi.org/10.15359/REE.24-3.13Widodo, H. P. (2014). Methodological considerations in interview data transcription. International Journal of Innovation in English Language, 3(1).Wijaya, Candra., Dalimunthe, Rasyid Anwar., & Muslim. Parents’ Perspective on The Online Learning Using Zoom Application in Early Childhood Education. JPUD: Jurnal Pendidikan Usia Dini, Volume 15 Number 2. DOI: https://doi.org/10.21009/JPUD.152.06Winship, M., Standish, H., Trawick-Smith, J., & Perry, C. (2021). Reflections on practice: Providing authentic experiences with families in early childhood teacher education. In Journal of Early Childhood Teacher Education (Vol. 42, Issue 3). https://doi.org/10.1080/10901027.2020.1736695